Identification and geovisualization of morphological-hydrographic changes in the area of the open pit "Turija" - Smajić, Sabahudin; Hadžimustafić, Edin; Kadušić, Alma (Journal for Geography, 2018)
In this paper morphological-hydrographic changes in the area of the coal open pit "Turija" in Banovići basin (north-eastern Bosnia and Herzegovina) are researched. The study was based on the field data and comparative analysis of topographic maps, satellite images, Digital Elevation Model and situational plans of the open pit area. With conducted GIS analysis of natural and anthropogenic relief of open pit "Turija" the changes in the structure of hypsometric level, slope and aspect, and the changes in the surface hydrographical network etc. are determined. The general trend of ground levelling, decrease in altitude differences, gradual disappearance of physical micro relief, disappearance of geomorphologic boundaries on the surface, disorganization of hydrographical network, the development of positive and negative forms of relief, and greater presence of physical-anthropogenic processes and forms in relation to physical ones are determined. Reduction of territories with southerly, easterly and westerly aspects, and a significant increase in territories with northerly aspect is also determined. Geospatial data obtained by GIS after their analytical and synthetic processing are geovisualized. Ten thematic maps were made and they provide insight into resulted changes in the researched geographical area. The explored indicators can serve as a significant factor in the future planning and selection of the type of re-cultivation of degraded areas in the area of research.